Enhanced magnetic properties and MRI performance of bi-magnetic core–shell nanoparticles. Issue 81 (16th August 2016) - Cardona, Fernando Arteaga; Urquiza, Esmeralda Santillán; Presa, Patricia de la; Tobón, Silvia Hidalgo; Pal, Umapada; Fraijo, Patricia Horta; Yacaman, Miguel José; Lozada Ramírez, José Daniel; Ivkov, Robert; Angulo-Molina, Aracely; Méndez-Rojas, Miguel Ángel
Abstract : Two sets of bi-magnetic, biocompatible Zn0.5 Mn0.5 Fe2 O4 @Fe3 O4 core–shell nanoparticles with enhanced magnetic properties were prepared. These bi-magnetic nanoparticles have a vast potential as MRI contrast agents. Abstract : Two sets of bi-magnetic Zn0.5 Mn0.5 Fe2 O4 @Fe3 O4 core–shell nanoparticles were prepared by a seed-mediated modified co-precipitation method. While the first set was obtained by fast addition of the alkaline solution to grow Fe3 O4 shells over the ferrite seeds, a slow drop-wise addition of stoichiometric Fe 2+ /Fe 3+ ion solution to the alkaline ferrite seeds solution was adopted to synthesize the second set. Samples were characterized by electron microscopy (STEM, TEM, UHRTEM) and magnetometry measurements. Viability MTT assay of the nanoparticles on L929 murine fibroblasts were performed, indicating that they are biocompatible. The coating of the Zn0.5 Mn0.5 FeO4 nanoparticle by a magnetite or maghemite shell minimizes the effect of the magnetic dead layer at the core surface, improving the magnetic properties and offering thus outstanding values for biological application. Relaxometry values r 2 higher than 300 mM −1 s −1 at H 1.5 T, and cell viability at concentrations as high as 0.5 mg mL −1 means these bi-magnetic nanoparticles have a vast potential as MRI contrast agents.